2023
DOI: 10.3389/fnins.2023.1047778
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier endothelial cells in neurodegenerative diseases: Signals from the “barrier”

Abstract: As blood–brain barrier (BBB) disruption emerges as a common problem in the early stages of neurodegenerative diseases, the crucial roles of barrier-type brain endothelial cells (BECs), the primary part of the BBB, have been reported in the pathophysiology of neurodegenerative diseases. The mechanisms of how early vascular dysfunction contributes to the progress of neurodegeneration are still unclear, and understanding BEC functions is a promising start. Our understanding of the BBB has gone through different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 151 publications
0
15
0
Order By: Relevance
“…Importantly, although brain endothelial cells are not the primary immune cells in the brain, they are known to participate in inflammatory responses at the brain barriers both in health and disease. , Correspondingly, a recent transcriptomic analysis revealed that many of the top AD-risk genes identified in genome-wide association studies (GWAS), which are microglia-specific in mice, are in fact expressed at higher levels in human BEC and other vascular cell types, suggesting that in mice and humans, there is a partial transfer of risk genes and pathways associated with AD from microglia to the vasculature during the process of evolution . This provides important evidence for the evolutionary-unique, human-specific role of BEC and cerebrovasculature in brain neuroimmunity in AD and justifies efforts of antineuroinflammatory drug candidate screening in BEC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, although brain endothelial cells are not the primary immune cells in the brain, they are known to participate in inflammatory responses at the brain barriers both in health and disease. , Correspondingly, a recent transcriptomic analysis revealed that many of the top AD-risk genes identified in genome-wide association studies (GWAS), which are microglia-specific in mice, are in fact expressed at higher levels in human BEC and other vascular cell types, suggesting that in mice and humans, there is a partial transfer of risk genes and pathways associated with AD from microglia to the vasculature during the process of evolution . This provides important evidence for the evolutionary-unique, human-specific role of BEC and cerebrovasculature in brain neuroimmunity in AD and justifies efforts of antineuroinflammatory drug candidate screening in BEC.…”
Section: Discussionmentioning
confidence: 99%
“…First, it presents a unique possibility to evaluate the antineuroinflammatory properties of novel compounds on the level of AD patient brain endothelial cells, previously not easily accessible to drug candidate screening efforts. With BBB neuroinflammation and neurodegeneration being closely linked in AD development and progression, , the discovery of such compounds may prove therapeutically useful in AD patients and lead to the identification of novel treatment avenues for AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The selective permeability of the BBB is orchestrated by tight junctions between endothelial cells, creating a daunting barrier that regulates the passage of ions, nutrients, and other essential substances crucial for proper brain function. 1,2 Understanding the intricacies of the BBB is pivotal not only for unraveling the mysteries of neurological health but also for developing targeted therapies for neurological disorders, as the barrier poses a formidable challenge for drug delivery to the brain. 1−4 The BBB plays a pivotal role in drug discovery, presenting both challenges and opportunities for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Transport function is based on a few paths of penetration of the BBB by specific compounds, and these paths will be further reviewed later. It is commonly known that both described functions of this structure are impaired in cases of neurodevelopmental and neurodegenerative disorders, such as Alzheimer's Disease and amyotrophic lateral sclerosis [2,3]. According to recent studies, the loss of integrity of the BBB is a cause of neurodevelopmental disorders including autism spectrum disorder (ASD) [4] or schizophrenia [5].…”
Section: Introductionmentioning
confidence: 99%